2021
DOI: 10.1021/acs.energyfuels.1c00308
|View full text |Cite
|
Sign up to set email alerts
|

Hopping Electrochemical Supercapacitor Performance of Ultrathin BiOCl Petals Grown by a Room-Temperature Soft-Chemical Process

Abstract: The use of easy synthesis methodology, high performance, and stable electrode materials is mandatory while developing potential energy storage devices on a mass scale. In the present work, room-temperature operating, a simple solution method is employed for obtaining ultrathin bismuth oxide chloride (BiOCl) supercapacitor electrode material over 3D nickel-foam. This free-standing BiOCl ultrathin petal-type electrode material was characterized for confiming the crystal strcture, surface morphology, and surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The energy and power densities are the key parameters that determine the practical utilization of the supercapacitor device based on its electrochemical performance. The Ragone plot determines the relation between the energy and power densities of the fabricated supercapacitor compared with previously reported literature as depicted in Figure f. The fabricated Biene/Sbene//AC HSC delivers competitive energy densities of 131.44, 126.75, 119, 69.7, and 43.1 Wh/kg, and their corresponding power densities are 1678, 2700, 5950.2, 6340.7, and 8262.2 W/kg at current densities of 2, 4, 6, 8, and 10 A/g respectively. To elucidate the practical applicability of the Biene/Sbene//AC HSC, an experiment was performed by connecting the red LED and charging it for 30 s using a 9 V battery .…”
Section: Results and Discussionmentioning
confidence: 73%
“…The energy and power densities are the key parameters that determine the practical utilization of the supercapacitor device based on its electrochemical performance. The Ragone plot determines the relation between the energy and power densities of the fabricated supercapacitor compared with previously reported literature as depicted in Figure f. The fabricated Biene/Sbene//AC HSC delivers competitive energy densities of 131.44, 126.75, 119, 69.7, and 43.1 Wh/kg, and their corresponding power densities are 1678, 2700, 5950.2, 6340.7, and 8262.2 W/kg at current densities of 2, 4, 6, 8, and 10 A/g respectively. To elucidate the practical applicability of the Biene/Sbene//AC HSC, an experiment was performed by connecting the red LED and charging it for 30 s using a 9 V battery .…”
Section: Results and Discussionmentioning
confidence: 73%
“…Semiconductor photocatalytic technology, as one of the most appealing green and environmentally benign technologies, has been explored to tackle environmental issues involving the elimination of organic pollutants, decomposition of water to hydrogen, and CO 2 photo-reduction for fuels. 2,3 Until now, abundant photocatalysts have been widely investigated for sewage treatment and air purication.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the pseudo and battery-like types are the characteristics of Faradaic materials that allow ion intercalation or redox reactions. , Although Faradaic materials enjoy a higher specific energy than the EDL counterparts, they usually suffer from lower power density and cycling instability due to the decomposition and/or corrosion of the electrode materials in high potential windows. In this regard, hybrid electrodes that contain both carbon materials and faradic materials have been proposed. Tian et al studied MoS 2 /MoO 2 nanoparticles grown on the surface of CNTs, which showed a capacitance of 228.4 F/g at 0.5 A/g, a specific energy of 11.88 Wh/kg, and a specific power of 2 kW/kg with high cycling stability in KOH electrolyte at 0.55 V . Samuel et al used a Zn 2 SnO 4 /SnO 2 /CNTs nanocomposite as a supercapacitor electrode that exhibited a capacitance of 260 F/g at 10 A/g in 6 M KOH and a potential window of 1 V .…”
Section: Introductionmentioning
confidence: 99%